Untersuchung und Bewertung des Erosionsrisikos für traditionelle und moderne Bewirtschaftungssysteme in der Region Castilla-La Mancha - Kappas, Martin; Schweter, Martin (ERDKUNDE, 1997)
Traditional land use is more and more being replaced by modern land use systems. This transformation process can lead to a loss of soil and substrate. The consequences are not clearly foreseen for the agricultural landscape and depend on the recurring exploitation of the land. Extensive change in the exploitation of the land happened during the last years in the mediterranean landscape. Especially the development of the irrigation agriculture in the La Mancha of Spain led to decisive alteration in the agricultural landscape. The present study tries to find out the erosion-endangered regions as well as the land use systems that increase erosion for a square region of 30 km length on the Campo de Montiel in the region of Castilla-La Mancha in the Meseta of Spain. The essential factors for erosion risks are identified. With the help of the assessment of these essential factor recommendations for the future use of the landscape should be established. The concept of the investigation contains the exploitation and combination of different data- and information layers for the calculation of a risk-map for the entire study area. The GIS-based model of the potential soil erosion amounts is estimated by the use of the Universal Soil Loss Equation (USLE), which is comparatively suitable because of its easy structure for the integration into GIS. Comparative investigations of various erosion models showed that physical and mathematical complex models are only insignificantly more precise than the simple and often used USLE (de Roo 1993). The potential erosion amount (t/ha * y) was calculated and finally classified into five risk classes. The USLE was selected since the necessary input parameters are easy to record. For the survey of the input parameters the following data layers are used: field survey, available data and maps and remote sensing (e.g. Fig. 1). In the study area different kinds of land use occur: Matorral, traditional permanent cultivation (traditional dry farming) and intensive irrigation farming (Center Pivots) in comparable relief positions and largely homogeneous geological subsoil. These particular conditions allow the isolation the impact of the single type of land use for soil erosion. The influence of the particular cultivation and cultivation techniques on soil erosion can directly be compared with each other. Hence people have a tool for future-decision making and planning considering change of land use. The possibilities of the model and the working method chosen in the GIS are shown with the help of two scenarios (scenario I: complete conversion of the traditional dry farming into irrigation farming; scenario II: zero-variant, conversion of current irrigation fields into dry farming).